Choosing approximation function for the model of settlement load curve, in static load test for precast concrete piles - Meyer, Zygmunt; Szmechel, Grzegorz (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
The main aim of the work is to define better correlation between parameters of Meyer- Kowalów equation [7,8] with the use of mathematical experiments and statistical tests. So far the research has shown that correlation between particular factors are different than common assumed. It was necessary to check non linear correlations between C-constant and k. A certain constant and starting data were assumed in the theoretical model applied to the paper. As a result of the mathematical experiments, the best fit proposal of estimation C and equation representingk=k(Ngr)was formulated.